Preparation and Characterization of Dinuclear Nickel(II) Complexes Containing N3Ni(μ1, 3‐SO3R)2(μ‐RCN4)NiN3 Cores: Crystal Structures and Magnetic Properties1. Issue 3 (18th February 2013) - Lach, Jochen; Perlt, Eva; Kirchner, Barbara; Kersting, Berthold
Abstract The preparation and characterization of three new mixed ligand macrocyclic [Ni2L2(L′)]+ complexes are described, where (L2)2– represents a supporting macrocyclic hexaaza‐bis(phenylsulfonato) ligand and L′ a tetrazolato ligand. The complexes [Ni2(L2)(CN4H)]BPh4 (4), [Ni2(L2)(CN4Me)]BPh4 (5), and [Ni2(L2)(CN4Ph)]BPh4 (6) were synthesized by H2O2 oxidation of the corresponding [Ni2(L1)(CN4H)]BPh4 (1), [Ni2(L1)(CN4Me)]BPh4 (2), and [Ni2(L1)(CN4Ph)]BPh4 (3) complexes supported by the corresponding hexaaza‐bis(thiophenolate) macrocycle. The compounds were characterized by means of elemental analysis, mass spectrometry, IR, and UV/Vis spectroscopy. The crystal structures of compounds 4–6 show that the bridging thiophenolate functions in 1–3 are in all cases converted to μ1, 3‐bridging sulfonate groups to generate N3Ni(μ1, 3‐SO3R)2(μ‐RCN4)NiN3 cores. The conversion to the phenylsulfonato groups is accompanied by a drastic increase of the Ni···Ni distances from 3.455(1) Å in 1, 3.425(1) Å in 2, and 3.443(1) Å [3.450(1) Å] in 3 to 4.2796(5) Å [4.3375(6) Å] in 4, 4.3402(6) Å in 5, and 4.2607(4) Å in 6. Upon oxidation the magnetic properties are affected. In contrast to 1–3, which exhibit an intramolecular ferromagnetic exchange interaction (S = 2 ground state), the spins of the nickel(II) (Si = 1) ions in 4–6 are antiferromagnetically coupled, the coupling constants J being –1.39 cm–1 (4), –1.43 cm–1 (5), and –1.60 cm–1 (6) (H = –2JS1S2) to yield a diamagnetic S = 0 ground state. DFT (density functional theory) calculations were carried out to substantiate the experimental results.